Quality of Life of Patient with Hypertension in Primary Health Care in Bandar Lampung - Sudewi Mukaromah Khoirunnisa; Atika Dalili Akhmad (Indonesian Journal of Pharmacy, 2019)
The high prevalence of hypertension in Indonesia, encourages studies related to how the quality of life of patients with hypertension. The purpose of this study was to measure quality of life, identify and explain factors related to the quality of life of patients with hypertension.The study design was descriptive correlation using a cross sectional study approach. The study subjects were all outpatient hypertensive patients several health centers in Bandar Lampung. The instrument used in this study was the Indonesian SF-36. The data collected included the patient's demographic characteristics including gender, age, education, occupation, and marital status, and the fields related to the health history of the study subjects included the duration of hypertension, complications, and the number of antihypertensive drugs consumed. Data were analyzed using bivariate analysis to see the relationship between two variables with the level of significance used was 5% (α = 0.05) with the value of the confidence interval set was 95%. Multivariate analysis was conducted to study the relationship of several independent variables with one or several dependent variables.The results of univariate analysis showed that age, marital status, duration of illness, complications, and the number of drugs consumed had an effect on the quality of life of hypertensive patients (p <0.05). The results of multivariate analysis showed that the factors of age, marital status, and duration of hypertension are factors that influence the physical domain, while the factors of gender, marital status, duration of hypertension, complications, and the number of drugs are influential factors in the mental domain mental.